Estresse, Burnout e estratégias de enfrentamento: um estudo com professores de uma instituição educacional privada de São Paulo - Biazzi, Sideli (2013)
Working is a resource of social integration that fosters personal development and brings important benefits, but in face of strong tensions it may lead to disorders such as stress and burnout syndrome. Stress is still perceived as a hard controlling factor that negatively affects workers lives, especially those under adverse psychosocial conditions. The balance between daily working activities and stress is essential for mental health, deserving special care when the worker exerts influence in people education, as happens with teachers. The objective of this research is investigating the occurrence of stress and burnout symptoms in the population of teachers in private elementary schools in Greater São Paulo, seeking for a possible connection with the use of coping strategies. The research studied a population of 427 teachers with the aid of ISS-LIPP, MBI and Brief-COPE in order to evaluate the impact of stress, burnout and coping strategies on teacher s health. Data show that 50.53% of the subjects were stressed, mostly in the stage of resistance (40.7%) with prevalence of psychological distress (32.5%). In addition, they indicate that 15.1% of the sample were under burnout, evidencing an association between stress and burnout. Women were a predominant part of studied population (81.7%), showing a higher percentage of stress during the stage of resistance when compared to men (p <0.0001). It was also verified that coping skills play an important role in the modulation of stress and burnout, as the more adaptive and active are the choices of coping strategies for teachers, the lower the levels of stress and burnout. The results validate the initial theoretical propositions of the study and point out the opportunity for a more thorough study of the theme, aiming to expand the repertoire of solutions for the improvement of teacher s life quality